2020
DOI: 10.1590/1806-9282.66.s2.86
|View full text |Cite
|
Sign up to set email alerts
|

The effect of abo and rh blood group antigens on admission to intensive care unit and mortality in patients with COVID-19 infection

Abstract: SUMMARY AIM The aim of this study is to analyze the prognostic significance of ABO and Rh blood group antigens along with various parameters in patients followed-up with the diagnosis of COVID-19. METHODS We evaluated 397 patients who were follow-up and treated due to COVID-19 infections. The ages, genders, chronic diseases, ABO and Rh blood group antigens, admission rates to Intensive Care Units (ICU), and mortality rates of the patients were analyzed. FINDINGS The mean age of the 397 patients with COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 7 publications
2
24
1
3
Order By: Relevance
“…In literature, there are studies investigating the effect of blood groups on clinical prognosis of patients. In the study by Juyi et al, the rate of hospitalization was higher in patients with A blood groups in SARS-CoV-2infection and in another study, the rate of Rh positivity was reported to be higher in patients hospitalized in the intensive care unit (ICU) (20,21). Our data are similar to findings in these studies.…”
Section: Resultssupporting
confidence: 90%
“…In literature, there are studies investigating the effect of blood groups on clinical prognosis of patients. In the study by Juyi et al, the rate of hospitalization was higher in patients with A blood groups in SARS-CoV-2infection and in another study, the rate of Rh positivity was reported to be higher in patients hospitalized in the intensive care unit (ICU) (20,21). Our data are similar to findings in these studies.…”
Section: Resultssupporting
confidence: 90%
“…Another similarity between adult and pediatric infected patients admitted to PICU is the high percentage of blood group A as previously reported by Yaylac et al; a similar trend was observed in our study. 35 Additionally, comorbidities affected the PICU admission and length of stay significantly. In our cohort, co-morbid conditions were recorded in 26 (60.5%) patients, with malignancy being the commonest (20.9%).…”
Section: Discussionmentioning
confidence: 99%
“…In various studies, it has been shown that in addition to blood groups' role in being infected with SARS-CoV-2, they may also affect the outcome of the illnesses. In their study Yaylaci et al [21] defined that ICU admission was higher in rate with the Rh (+) blood group (p=0.011), but no meaningful association was found between mortality and blood groups or Rh factors (p>0.05). In another study with 14112 participants, Zietz and Tatonetti [18] (2020) showed that the risk of intubation was significantly reduced in blood Groups A and marginally increased in blood Groups AB and B.…”
Section: Discussionmentioning
confidence: 91%